2024
DOI: 10.1021/acs.energyfuels.3c04258
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery Using Polymer Alternating CO2 Gas Injection: Mechanisms, Efficiency, and Environmental Benefits

Shubham Prakash,
Dinesh Joshi,
Keka Ojha
et al.

Abstract: In light of the depletion of conventional oil reserves and rising global warming, the CO 2 -EOR has garnered global attention among stakeholders for its potential to evolve into a net carbon-negative technique for extracting residual oil. CO 2 -EOR is a method of extracting additional crude oil beyond primary and secondary recovery from the reservoir using CO 2 as an injection fluid. Among CO 2 -EOR methods, water alternating gas (WAG) injections have been adopted in over 90% of CO 2 -EOR projects worldwide du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In this process, the polymer facilitates oil movement toward production wells by alternating with CO 2 to displace oil. 90–92 The conversion of the CA-captured PAA into the polymer surfactant is accompanied by CO 2 release, which can be controlled by adjusting the ratio of the ion exchanger. The ion exchange in water causes the surfactant to self-assemble into nanoobjects, which are expected to effectively displace oil when used in the PAG injection method.…”
Section: Resultsmentioning
confidence: 99%
“…In this process, the polymer facilitates oil movement toward production wells by alternating with CO 2 to displace oil. 90–92 The conversion of the CA-captured PAA into the polymer surfactant is accompanied by CO 2 release, which can be controlled by adjusting the ratio of the ion exchanger. The ion exchange in water causes the surfactant to self-assemble into nanoobjects, which are expected to effectively displace oil when used in the PAG injection method.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of CO 2 – EOR can be done under several schemes, including the injection of miscible/immiscible CO 2 , water alternating CO 2 gas injection (WAG CO 2 ), polymer alternating gas CO 2 (PAG), simultaneous water CO 2 gas injection, foam assisted CO 2 , low salinity water–surfactant–CO 2 , and hybrid schemes with surfactant polymer (SP). Most CO 2 – EOR processes are commonly confronted to satisfy two objectives consisting of maximizing ORF and minimizing the production of CO 2 (this latter means the increase in the storage performance). However, it is worth mentioning that many published studies and experimental tests demonstrated the superiority of the miscible type (single–phase flow) of CO 2 – EOR processes in reaching higher ORF compared to the immiscible type (two–phase flow). , The suitable design of a CO 2 – EOR process depends greatly on the so-called minimum miscibility pressure (MMP) since this parameter allows the determination of the injection type, i.e., miscible or immiscible. MMP represents the cutoff pressure at reservoir temperature (T R ) above which miscibility between the reservoir fluid and the injected gas occurs after multiple contacts. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted to modify the oil-wet and/or CO 2 -wet reservoirs using various chemicals, including surfactants, nanofluids, acids like stearic acids, pH-altering agents, and smart fluids with variations in ionic composition. ,,, These chemicals demonstrated a significant alteration in wettability, thereby improving the ultimate storage potential of CO 2 through capillary and structural mechanisms. However, concerns regarding the economic feasibility, scalability, and deliverability of such chemicals deep within reservoirs present several challenges.…”
Section: Introductionmentioning
confidence: 99%